Evaluation of Dermoscopic Patterns of Vesiculobullous Disorders - Namita D Narkhede; Balakrishna Nikham; Varsha Jamale; Asma Hussain; Mohan Kale (Wolters Kluwer Medknow Publications, 2021)
Background: Clinical diagnosis of vesiculobullous disorders (VBD) is not always straightforward. It is a challenge for a dermatologist to make the right diagnosis noninvasively in a short time. Objective: To evaluate dermoscopic patterns associated with vesiculobullous disorders. Methods: A total of 230 patients, irrespective of age and gender, with a history and clinical presentation suggestive of VBD (including primarily infectious, inflammatory, genetic, antibody-mediated, mechanical, environmental, metabolic, and drug-related) were recruited into the study. Patients with secondarily infected lesions were excluded. Dermoscopic examination along with Tzanck smear/skin biopsy smear test was performed on the most representative lesions. Data were compiled and statistically analyzed using SPSS version 21.0. Results: Lesions with erythematous (vascular) and yellowish (serum) translucent background with regular margins were seen in most of the VBD studied. Chickenpox (CP) and herpes zoster (HZ) lesions evolved with the progress of their clinical stages. Follicular and eccrine openings were commonly seen, but the pigmentation around them was specific to pemphigus vulgaris. A distorted pigment network was noted in bullous pemphigoid. White rosettes (keratin blockage) were characteristic of epidermolysis bullosa, Wickham striae (orthokeratosis) of lichen planus, and crumpled fabric appearance (flaccidity) of Hailey-Hailey disease. Globules/dots (microvesicles) of different colors were also seen in various VBD. Blue/black color usually corresponded to retained melanin. Conclusion: Some dermoscopic patterns are observed consistently with certain diseases, and these can be used for their diagnosis, complementary to histopathological examination.